2011
DOI: 10.1016/j.str.2011.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Recognition of Phosphorylated Histone H3 by the Survivin Subunit of the Chromosomal Passenger Complex

Abstract: Localization of the chromosomal passenger complex (CPC) at centromeres during early mitosis is essential for accurate chromosome segregation and is dependent on the phosphorylation of histone H3. We report the 2.7 Å resolution structure of the CPC subunit Survivin bound to the N-terminal tail of histone H3 carrying the Thr3 phosphorylation mark (Thr3ph). The BIR domain of Survivin recognizes the Ala1-Arg2-Thr3ph-Lys4 sequence, decoding the modification state and the free N terminus of histone H3 by a strategy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
117
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(129 citation statements)
references
References 49 publications
12
117
0
Order By: Relevance
“…Consistently, neither ING4 nor SGF29 showed detectable binding to a corresponding NS1 peptide (Table 1). Another example is Survivin, which specifically recognizes phosphorylated H3T3 and also requires the free N-terminal amine of H3 for interaction 16 . Why is CHD1 able to recognize the methylated 226 ARSK 229 motif of NS1 in a C-terminal context?…”
Section: Resultsmentioning
confidence: 99%
“…Consistently, neither ING4 nor SGF29 showed detectable binding to a corresponding NS1 peptide (Table 1). Another example is Survivin, which specifically recognizes phosphorylated H3T3 and also requires the free N-terminal amine of H3 for interaction 16 . Why is CHD1 able to recognize the methylated 226 ARSK 229 motif of NS1 in a C-terminal context?…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that binding of Survivin to the phosphorylated form of the histone H3 N-terminus (H3-T3ph) is essential in CPC formation [21]. Survivin has an available binding site on its BIR domain to identify H3-T3ph.…”
Section: Docking Of Phosphorylated Histone H3 To Survivinmentioning
confidence: 99%
“…2J) are traceable to the LECA (Lloyd et al 2009;Zippo et al 2009;Garcia-Alai et al 2010;Singh et al 2012). However, the histone H3T3-binding BIR domain appears to be a later innovation in eukaryotic evolution, probably emerging concomitantly with haspin-like kinases that modify the position recognized by them (Jeyaprakash et al 2011).…”
Section: Provenance Of Eukaryotic Epigeneticsmentioning
confidence: 99%